Tetrakis-Phthalocyanines Bearing Electron-Withdrawing Fluoro Functionality: Synthesis, Spectroscopy, and Electrochemistry - ÖZKAYA, ALİ RIZA (WILEY-HINDAWI, 2009)
In this study, 2,9,16,23-tetrakis-4'(2,3,5,6-tetrafluoro)-phenoxy-phthalocyaninato-metalfree and metal(H) complexes, (H(2)PcBzF(16), ZnPcOBzF(16), CuPcOBzF(16), and CoPcOBzF(16)) (Bz: Benzene) (2H, Zn, Cu, and Co), have been prepared directly from the corresponding 4'-(2,3,5,6-fluorophenylthio)-phthalonitrile compounds in the presence of 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) in high boiling quinoline solvent. Tetrafluoro atoms on 2,3,5,6-position of benzene at the peripheral sites of phthalocyanines (Pcs) give rise interesting solubility to tetrakismetallophthalocyanines. Although all complexes were soluble in DCM, CHCl3, THF, DMF, and DMSO with increasing order, complexes synthesized, particularly H(2)PcBzF(16), CuPcOBzF(16), have very limited solubility in DMF and DMSO. The complexes have been characterized by elemental analysis, FTIR, H-1 NMR, UV-vis, and MALDI-TOF mass spectral data. The cyclic voltammetry and differential pulsed voltammetry of the complexes show that while H(2)PcBzF(16), CuPcOBzF(16), and ZnPcOBzF(16) give ligand-based reduction and oxidation processes, CoPcOBzF(16) gives both ligand and metal-based redox processes, in harmony with the common metallophthalocyanine complexes. Redox processes due to both aggregated and disaggregated species were simultaneously observed during the first reduction process. The nature of the metal-based redox processes was confirmed using spectroelectrochemical measurements. (C) 2009 Wiley Periodicals, Inc. Heteroatom Chem 20:262-271, 2009; Published online in Wiley InterScience (www.interscience.wiley.com). DOI 10.1002/hc.20545
Keywords: SUBSTITUTED COBALT; METALLOPHTHALOCYANINES; MANGANESE